Role of Swiss Law on the FIFA Judicial Process - Youyuenyong , Pedithep (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
A formal way for Fédération Internationale de Football Association (FIFA) to deal with sport-related disputes derive from the FIFA Statutes. It creates a minimum standard for regulatory and disciplinary actions which every confederation and affiliated member associations of FIFA must meet. One way to ensure that FIFA will meet a minimum standard is by placing a list of comprehensive, clear and reasonable fundamental principles of dispute resolution in the FIFA Statutes and publishing an accompanying statutory policy statement setting out how all relevant stakeholders should be interpreted and applied. FIFA is an exclusive jurisdiction to organise international football competitions and oversee all aspects of the global football actions with strong Swiss law influences. FIFA is an autonomous jurisdiction with strong Swiss law influences. The legal aspects of the FIFA Statutes were derived from the concept of Swiss substantive and procedural rules, which generally appears in legal terms at the confederation, national and local levels. Swiss law underpins self-regulatory regime of FIFA and shapes procedure or proceedings for interpreting and enforcing the FIFA Statutes. The analyses of this paper were carried out on the basis of the FIFA’s literature on the subject, as well as Swiss substantive and procedural rules common source of law in global football disputes. It was also indicated that it is possible in the situation of treating the legal aspects of dispute resolution in global football in terms of the FIFA’s proceedings and allows its application not only at the level of FIFA rules, but also at the confederation, national and local levels.